Effects of Gliricidia sepium residue vermicompost on the yield and dry matter biomass of organic choy sum mustard - Masri, Intan Nadhirah; Sadi, Tosiah; Karam, Daljit Singh; Abdul Sukor, Arina Shairah; Basir, Mohamed Hafeifi; Rajoo, Keeren Sundara; Abdu, Arifin (Malaysian Society of Applied Biology, 2022)
As the population grows and resource consumption increases, waste management has become a significant environmental challenge. A more sustainable approach to waste management is essential to maximize the recovery of materials acquired from nature. Vermicomposting is one of the answers to sustainable waste management. A study was conducted to determine the viability of vermicomposting Gliricidia sepium leaves and office scrap paper with matured compost as feedstock and to determine the vermicompost characteristics and suitability as potting mixtures for vegetable cultivation. The choy sum mustard was selected as the test crop. The plants were grown in the pots in a netted nursery in Serdang, Selangor. Treatments were mixtures of vermicompost to soil ratio by volume: control (0% no vermicompost), T1 (20% vermicompost), T2 (40% vermicompost), T3 (60% vermicompost), T4 (80% vermicompost) and T5 (100% vermicompost). Physicochemical properties of the potting media mix were determined and compared to an established growth media concentration and other ASEAN standards. Crop growth was evaluated by measuring plant height, the number of petioles, and fresh and dry weights at harvest. A significant improvement in the physicochemical properties of the media was observed, where the optimum ratio of potting media was 60% to 80% (T3 & T4). The number of petioles was 20-46% higher, plants were 39-46% taller, and dry matter accumulation was three-fold higher than controls. Crop yields were 200% higher in media treatments consisting of 60-80% vermicompost. In conclusion, G. sepium based vermicompost could be used in media mixtures for potting plants.